Negative Affect, Type D Personality, Quality of Life, and Dysfunctional Outcomes of Total Knee Arthroplasty - Matthias Vogel; Christian Riediger; Martin Krippl; Jörg Frommer; Christoph Lohmann; Sebastian Illiger (Pain Research and Management)
Background. Type D personality (TDP) is a sign of tapered stress and compromises treatment outcomes including those of hip arthroplasty. The common dissatisfaction with total knee arthroplasty (TKA) is predicted by fear avoidance, pain catastrophizing and emotional lability, with poor quality of life (QoL) reflecting these strains. This study is the first to investigate the influence of TDP on TKA assuming (1) negative affect (NA) to be linked to fear avoidance and to increased dissatisfaction with TKA and (2) the expression of NA and social inhibition (SI) to not be stable over time. Method. We studied 79 participants using the brief symptom inventory-18, the pain-catastrophizing scale, the Tampa scale of kinesiophobia, the SF-36, and the WOMAC preoperatively and 12 months postoperatively. T-test and regression were used to compare the variables of interest between groups built based upon outcome severity. Result. NA at follow-up predicted knee pain (p=0.02) and knee function (p<0.01) at follow-up. Contrarily, increased expressions of NA/SI at follow-up were predicted by NA (p=0.04) and rumination (p=0.05) at the baseline. Conclusion. The present results suggest the postoperative increase of NA to be linked to dysfunctional outcomes of TKA due to an interaction with pain catastrophizing. Baseline self-rated physical health did not connect to the dissatisfaction with TKA 1-year postoperatively.